2009
DOI: 10.1186/1749-8090-4-59
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of matrix metalloproteinases -1,-2,-3 and -9 in thoracic aortic diseases and acute myocardial ischemia

Abstract: Background: Matrix metalloproteinases (MMPs) constitute a family of zinc-dependent proteases (endopeptidases) whose catalytic action is the degradation of the extracellular matrix components. In addition, they play the major role in the degradation of collagen and in the process of tissue remodeling. The present clinical study investigated blood serum levels of metalloproteinases-1, -2, -3 and -9 in patients with acute and chronic aortic dissection, thoracic aortic aneurysm and acute myocardial ischemia compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 26 publications
4
40
1
Order By: Relevance
“…In this study, only the MMP-9 serum level in the control group showed a weak positive correlation with age (correlation coefficient=0.375; P=0.016). Consistent with other studies, there were no significant differences in serum marker levels between men and women in the control group 29,41 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, only the MMP-9 serum level in the control group showed a weak positive correlation with age (correlation coefficient=0.375; P=0.016). Consistent with other studies, there were no significant differences in serum marker levels between men and women in the control group 29,41 .…”
Section: Discussionsupporting
confidence: 92%
“…Many different studies have investigated the serum levels of MMP-2, MMP-9 and VEGF in cancer patients with different and sometimes contradictory results 8,[24][25][26][27][28][29][30][31][32] . We wanted to incorporate these arguable markers into specific clinical events of two narrowly defined groups of cancer patients to prove or disprove their clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…MMP1 is thus a major peptidase of the MMP family and plays a prominent role in collagen degradation, specifically that of collagen type I, which is important for remodeling of the extracellular matrix and cell-matrix interactions (18). The serum concentrations of MMP1, MMP3, and MMP9 have been found to be increased in patients with acute aortic dissection (19). Expression of MMP1 and MMP9 was also shown to be increased in tissue affected by aortic aneurysm or dissection (20).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating concentrations of several matrix metalloproteinase types seem to be elevated in patients with acute dissection. 22 However, previous reports are challenging to interpret because they generally had small sample sizes, sources of comparison/control patients were often not described, and analyses were conducted with descriptive statistical methods without adjustment for other factors. Nonetheless, our results, together with those of Shinohara et al, 21 support the concept that elevated concentrations of circulating macromolecules found in aortic ECM could serve as biomarkers of thoracic aortic dissection.…”
Section: Odds Ratio (Or)mentioning
confidence: 99%
“…Fourth, more sensitive fibrillin assays are not currently available. Development of highly sensitive assays allowing quantitation of a full range of concentrations, by guest on May 12, 2018 http://circres.ahajournals.org/ Downloaded from especially at the low end where we expect normal levels to occur, will be required to better discriminate aortic dissection from other causes of chest pain. Fifth, the source of microfibril fragments detected in this study is unknown.…”
Section: Odds Ratio (Or)mentioning
confidence: 99%